A Note on High-Speed Rail Investments and Travelers' Value of Time - Lars Hultkrantz (Örebro University School of Business, 2012)
High-Speed Rail (HSR) is designed for travelers with high value of time. HSR offer fast and reliable services and good possibilities for work during the journey. Surprisingly, these benefits of HSR investment proposals are often appraised by use of travel-time valuations of people who use conventional (intercity) train services. The standard approach builds on two major assumptions, linearity of demand, and that the value of time is unchanged between the "before" and "after" alternatives, i.e., that change in the average value of time of passengers can be ignored. While the first of these is well known, the second is not always observed. However, the spread of values of time between individual travelers is large and is an essential motivation for HSR investments. This note therefore considers whether the assumption that the value of time remains unchanged by the speed improvement induces any significant bias in the appraisal. We first use a modal-mix model where travelers have varying value of time to outline some conceptual points and then discuss to what extent these may affect the social profitability of three recently constructed or proposed HSR lines: Oslo- Stockholm (Norway and Sweden), Stockholm-Göteborg (Sweden) and Beijing-Shanghai Hongqiao (China). We conclude that a RoHbased evaluation of an HSR line should be complemented by a sensitivity analysis of how the outcome is affected by possible changes of the composition of travelers with different values of time.
Keywords: D61; H43; L92; 330; Cost-benefit analysis; rule-of-a-half; high-speed rail